Penerapan Restitusi Sebagai Bentuk Perlindungan Hukum Terhadap Perempuan Korban Tindak Pidana Kekerasan Seksual - Andayani, Rizki; Chandra, Tofik Yanuar; Candra, Mardi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Sexual harassment is a crime that often occurs in society. This problem can happen to anyone, especially adult women and children. Acts of violence range from sexual harassment to sexual assault such as rape. This research uses a qualitative research method which is an in-depth understanding of a social or cultural phenomenon, meaning it examines the principles and norms of law based on primary and secondary legal materials, focusing on the main issue of legal protection for victims of sexual violence and the application of restitution for victims. The approach used in this research is a statutory approach and a case approach. The analysis process begins by categorizing the data and analyzing it to find the principles of regulations in legislation by analyzing the content and interpreting primary legal materials according to their context at the time of their creation. The study found that victims of violent crimes against women have the right to receive restitution, as stated in Indonesian laws. Victims can request restitution before or after a court's final decision. However, this right is not absolute and can vary depending on the circumstances. The researcher analyzed three court cases and found inconsistencies. In two cases, victims received different amounts of restitution. In the third case, the victim did not receive restitution because they hadn't requested it. The judges in this case focused on following legal procedures rather than prioritizing the victim's protection